Fifth Conference on Medical and Aromatic Plants of Southeast European Countries : 2.-5.9.2008, Brno, Czech Republic (Mendel University of Agriculture and Forestry Brno, 2008)
From 5th Conference on Medicinal and Aromatic Plants of Southeast european countries.
Keywords: Plants, Medicinal; Botany; farmakognozie; chemické techniky analytické; zemědělství a potravinářství; botanika; biodiverzita; léčivé rostliny; Chemistry Techniques, Analytical; Pharmacognosy; Evropa; Europe; Biodiversity